Frugal innovation : how to do better with less - Radjou, Navi; Prabhu, Jaideep (Gurgaon Hachette Book Publishing, 2015)
With a Foreword by Paul Polman, CEO, Unilever. Frugal innovation is a way that companies can develop high-quality products and create more value with limited resources. In today$1 (Bs cost-constrained environment, companies in the developed economies are seeking new routes to long-term business success - while also appealing to cost-conscious and environmentally-aware consumers. With an estimated trillion-dollar global market for sustainable products, and with potentially huge cost savings to be gained, frugal innovation is revolutionising business and reshaping management thinking. This seminal book gives an overview of the principles, perspectives and techniques behind frugal innovation, connecting with key contemporary business concepts such as the sharing and circular economies and the maker movement. It offers a blueprint for leaders and managers in companies of all sizes and across all sectors on how to profit from doing business frugally. Based on the author$1 (Bs six key principles of frugal innovation, and packed with targeted advice and specific recommendations for business functions such as R&D, operations, HR and sales and marketing, Frugal Innovation is a masterclass in the art of doing more with less.s
Includes index
Keywords: Creative ability in business; Thriftiness